Vascular Endothelial Growth Factor-A Deficiency in Perivascular Adipose Tissue Impairs Macrovascular Function - Gharakhanian, Raffi; Su, Shi; Aprahamian, Tamar (Frontiers in Physiology, 2019)
Objective. Thoracic perivascular adipose tissue (PVAT) has been shown to release factors which influence the functioning of neighboring vascular tissue. Cardiovascular complications of obesity are on the rise, therefore, this study set out to determine if adipose-specific ablation of vascular endothelial growth factor-A (VEGF-A) plays a role in the maintenance of aortic structure and function. Methods. Adipose-specific VEGF-A deficient mice were previously generated. Fabp4cre(+).VEGFflox/flox and Fabp4cre(-).VEGFflox/flox mice were maintained on chow diet. PVAT gene expression was measured with real time quantitative PCR. Aortic vasomotor response was assessed with isometric tension measurements. Collagen deposition was analyzed histologically in the vascular media and compared using ratio metric pigment density. Results. PVAT-specific adiponectin expression was decreased in Fabp4cre(+).VEGFflox/flox mice. Isometric tension measurements revealed a dose-dependent dysfunction in response to acetylcholine within the distal aortic segment of Fabp4cre(+).VEGFflox/flox. Fabp4cre(+).VEGFflox/flox mice exhibited increased aortic deposition of collagen within the thoracic adventitial and medial spaces. Conclusion. These data demonstrate that decreased expression of VEGF-A within the surrounding adipose tissue microenvironment of thoracic aorta has a detrimental effect on aortic integrity and vascular function. Modulation of angiogenic pathways within PVAT may offer an important avenue towards the treatment of adipose tissue dysfunction in obesity and its vascular complications.